Hubungan Dukungan Keluarga Dengan Tingkat Depresi Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa Di PTPN X Rumah Sakit Gatoel Mojokerto - Pratiwi, Danies Tunjung (SEKOLAH TINGGI KESEHATAN MAJAPAHIT MOJOKERTO, 2013)
Depression is a psychological effect that is common in patients with chronic health problems such as ESRD (End Stage Renal Disease). Depression is often associated with increased morbidity of the disease. The results of preliminary studies that the researchers did found that 85% of patients with chronic renal failure undergoing regular hemodialysis in PTPN X Gatoel Hospital Mojokerto depressed. Strong support system can speed up recovery of depressive episodes. Family support would substantially increase a personâs adjustment to the events in live. The purpose of this study to determine the relationship of family support with levels of depression chronic renal failure patients undergoing hemodialysis. The research is Expost Facto Time Changes to the type of research Throhoc or Retrospectives. The population in this study were patients with chronic renal failure undergoing hemodialysis at PTPN X Gatoel Hospital Mojokerto by the number of samples taken by 30 respondents with non-probability sampling technique thst is consecutive sampling.The results showed that the majority (90%) patients with chronic renal failure undergoing hemodialysis were depressed with the largest proportion is mild depression (43%). Judging from the absence of family support is known that more than 50% get good family support. Spearman Rank Test results of the analysis results obtained p = 0,000 < Î± = 0,05, so Ha is received it means there is a relationships of family support with levels of depression chronic renal failure patients undergoing hemodialysis in PTPN X Gatoel Hospital Mojokerto. Family support is an important form of support system for patients who are depressed. Family support appropriate and as required improved the lives an improve quality of live. Families can always be expected to provide support so that patients can develop coping mechanism and problem solving are effective.Keywords : Family Support, Depression, GGK, Hemodialysis.